Using simulation to educate students about the culture of disability. Issue 6 (June 2021) - Strunk, Julie; Argenbright, Christine; Leisen, Melissa; Sawin, Erika Metzler; Kiser, Tammy; Donovan, Laureen
Abstract : Simulation techniques designed to educate nursing students about the culture of disability